STRATEGIC PLANNING FOR TOURISM VILLAGE DEVELOPMENT: ANALYSIS OF POTENTIALS AND PROBLEMS IN NOEPESU VILLAGE BARAT MIOMAFFO DISTRICT NORTH TIMOR TIMOR REGENCY (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to analyze and describe the potential and problems of developing a tourist village in Noepesu Village, West Miomaffo District, North Central Timor Regency. The type of research used is descriptive qualitative research with data collection techniques using Focus Group Discussion, observation, and documentation. The results of this study are that Noepesu Village has good potential to be developed both natural potential and community support, but also the Noepesu Village Government needs to anticipate problems that often occur, including the lack of educated human resources, the village community is not ready to accept change, the available facilities incomplete, not yet planned for the tourism model offered, the absence of Village Regulations as legality in developing tourist villages, the possibility of natural disasters and the disappearance of community customs, so an anticipatory plan is needed so that changes can be carried out without causing negative threats or impacts.